Rapid design exploration framework for application-aware customization of soft core processors - Prakash, Alok (2021)
Off-the-shelf soft core processors are becoming increasingly popular in embedded systems design today as they provide for application specific customization, in particular through instruction subsetting. However, choosing the right processor configuration remains a challenge as the search space becomes prohibitively large when the configurable options increase. In this paper we propose a framework to rapidly explore the processor configuration design space for a given application. Unlike existing approaches that require time-consuming synthesis process, the proposed method relies only on a single-pass output of the LLVM compiler infrastructure. Experimental results based on widely used benchmarks show that the proposed framework can reliably predict the actual performance and area trends of various configurable options. ©2009 IEEE.